Allergens of permanent hair dyes induces epidermal damage, skin barrier loss and IL-1 α increase in epidermal in vitro model. (February 2018) - Zanoni, Thalita Boldrin; Pedrosa, Tatiana Nascimento; Catarino, Carolina Motter; Spiekstra, Sander W.; de Oliveira, Danielle Palma; Den Hartog, Gertjan; Bast, Aalt; Hagemann, Geja; Gibbs, Susan; de Moraes Barros, Silvia Berlanga; Maria–Engler, Silvya Stuchi
Abstract: Allergic and irritant skin reactions caused by topical exposure to permanent hair dyes are a common problem. For regulatory and ethnical purposes, it is required to perform chemical safety assessment following the replacement, reduction, and refinement of animal testing (3Rs). Permanent hair dyes are formed by a mixture of ingredients that vary from low to extreme skin sensitizing potency and that inter-react to form unknown by-products. Because of the complex reaction, this cytotoxic mechanism has not yet been elucidated and is the subject of this study. Here, we topically exposed p -phenylenediamine (PPD), Resorcinol (RES), Hydrogen Peroxide (H2 O2 ) alone or as a mixture to RhE and evaluated parameters related to skin irritation such as epidermal viability, keratinocytes damage, barrier loss and IL-1 α. Our data indicates that ingredients tested alone did not lead to an increase of cytotoxic parameters related to skin irritation. However, when the mixture of PPD/H2 O2 /RES and PPD/H2 O2 was applied to the RhE, some of the parameters such as morphological changes including the presence of apoptotic cells, barrier loss and increased IL- 1 α release were observed. The results indicate that the mixture of ingredients used in permanent hair dyes have an irritant effect in RhE while the ingredients alone not. Highlights: Permanent hair dye formulations are formed by a complex mixture of skin sensitizers. The specific mechanism that leads to skin allergy and irritation remains unknown. Among other hair dyes, permanent are the most produced and consumed worldwide. Reconstructed skin models are efficient tools to screen toxicity of these dyes.